A Systematic Literature Review and Indirect Treatment Comparison of Efficacy of Repository Corticotropin Injection versus Synthetic Adrenocorticotropic Hormone for Infantile Spasms - Michael S. Duchowny; Ishveen Chopra; John Niewoehner; George J. Wan; Beth Devine (Journal of Health Economics and Outcomes Research)
**Background:** Infantile spasms is a rare disease characterized by distinct seizures and hypsarrhythmia. Adrenocorticotropic hormone (ACTH) is available as a natural product (repository corticotropin injection, [RCI]; Acthar® Gel) and as synthetic analogs. RCI is a naturally-sourced complex mixture of purified ACTH analogs and other pituitary peptides approved by the United States Food and Drug Administration as a monotherapy for the treatment of infantile spasms. RCI is commonly used in the United States. Outside the United States, synthetic analogs of ACTH—synthetic ACTH1-24 (tetracosactide) and synthetic ACTH1-39 (corticotropin carboxymethyl-cellulose [CCMC])—are used. The efficacy of RCI may differ from that of synthetic ACTH treatments based on the structure of peptide; however, no head-to-head clinical trials have compared the efficacy of RCI and synthetic ACTH treatments.